2015
DOI: 10.3390/ma8095280
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hydrogen Storage Tank Systems Based on Complex Metal Hydrides

Abstract: This review describes recent research in the development of tank systems based on complex metal hydrides for thermolysis and hydrolysis. Commercial applications using complex metal hydrides are limited, especially for thermolysis-based systems where so far only demonstration projects have been performed. Hydrolysis-based systems find their way in space, naval, military and defense applications due to their compatibility with proton exchange membrane (PEM) fuel cells. Tank design, modeling, and development for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 111 publications
(218 reference statements)
0
41
0
Order By: Relevance
“…Challenges of hydrogen storage are being addressed and hydrogen powered vehicles have been introduced to the commercial marketplace. [1][2][3][4] Unfortunately, the predominant fraction of hydrogen generated today is produced by steam reformation of fossil fuel by reacting the fossil fuel with steam to release H 2 and CO 2 . Steam reformation is a substantial source of CO 2 emissions, negating the climate mitigation effect of using H 2 as a fuel.…”
mentioning
confidence: 99%
“…Challenges of hydrogen storage are being addressed and hydrogen powered vehicles have been introduced to the commercial marketplace. [1][2][3][4] Unfortunately, the predominant fraction of hydrogen generated today is produced by steam reformation of fossil fuel by reacting the fossil fuel with steam to release H 2 and CO 2 . Steam reformation is a substantial source of CO 2 emissions, negating the climate mitigation effect of using H 2 as a fuel.…”
mentioning
confidence: 99%
“…The results of control were used to study hydrogen generation processes only and are not meant to address diagnosing tasks. Paper [5] gives information about hydrogen storage systems based on metal hydrides and intermetallic compounds. Such systems are employed in space engineering, transportation vehicles, military naval applications, due to their compatibility with the fuel elements of the proton exchange membrane (PEM).…”
Section: синтезовано алгоритм контролю технIчного стану генераторIв вmentioning
confidence: 99%
“…A solid-state metal hydride hydrogen storage canister with interesting features of low-pressure operation, safety and scalability and is potentially useful for transportable applications, such as compact portable or mobile systems [1]. In a light metal hydride tank system, the hydrogen uptake and release are governed by kinetic reactions that can be characterized by poor absorption/desorption kinetics [2].…”
Section: Introductionmentioning
confidence: 99%
“…A resistance analysis was performed by comparing the transport phenomena and intrinsic kinetics using a kinetic model from Lozano et al [17,18]. Ley et al [1] predicted that the driving force for hydrogen transportation, intrinsic kinetics and heat transfer can be the drawbacks during hydrogen sorption. The results indicated that hydrogen transportation has an insignificant effect (independent of the size of the reactor), that the intrinsic kinetics play a critical role in a small cell of 2 mm and that heat transfer is the main problem during absorption in a scale-up tank.…”
Section: Introductionmentioning
confidence: 99%